Doppler ultrasonography principles and methods of evaluation of the reproductive tract in mares - Jair Camargo Ferreira (Acta Scientiae Veterinariae, 2011)
Background: Doppler ultrasonography is a non-invasive real time pulse-wave technique recently used for the transrectal study of the reproductive system hemodynamics in large animals. This technic is based in the Doppler Effect Principle that proposes the change in frequency of a wave for an observer (red blood cells) moving relative to the source of the respective wave (ultrasonic transducer). This method had showed to be effective and useful for the evaluation of the in vivo equine reproductive tract increasing the diagnostic, monitoring, and predictive capabilities of theriogenology in mares. However, an accurate and truthful ultrasonic exam requires the previous knowledge of the Doppler ultrasonography principles. Review: In recent years, the capabilities of ultrasound flow imaging have increased enormously. The current Doppler ultrasound machines offer three methods of evaluation that may be used simultaneously (triplex mode). In B-mode ultrasound, a linear array of transducers simultaneously scans a plane through the tissue that can be viewed as a two-dimensional gray-scale image on screen. This mode is primarily used to identify anatomically a structure for its posterior evaluation using colored ultrasound modes (Color or Spectral modes). Colored ultrasound images of flow, whether Color or Spectral modes, are essentially obtained from measurements of moving red cells. In Color mode, velocity information is presented as a color coded overlay on top of a B-mode image, while Pulsed Wave Doppler provides a measure of the changing velocity throughout the cardiac cycle and the distribution of velocities in the sample volume represented by a spectral graphic. Color images conception varies according to the Doppler Frequency that is the difference between the frequency of received echoes by moving blood red cells and wave frequency transmitted by the transducer. To produce an adequate spectral graphic it is important determine the position and size of the simple gate. Furthermore, blood flow velocity measurement is influence by the intersection angle between ultrasonic pulses and the direction of moving blood-red cells (Doppler angle). Objectively colored ultrasound exam may be done on large arteries of the reproductive tract, as uterine and ovary arteries, or directly on the target tissue (follicle, for example). Mesovarium and mesometrium attachment arteries also can be used for spectral evaluation of the equine reproductive system. Subjectively analysis of the ovarian and uterine vascular perfusion must be done directly on the corpus luteum, follicular wall and uterus (endometrium and myometrium associated), respectively. Power-flow imaging has greater sensitivity to weak blood flow and independent of the Doppler angle, improving the evaluation of vessels with small diameters and slow blood flow. Conclusion: Doppler ultrasonography principles, methods of evaluation and reproductive system anatomy have been described. This knowledge is essential